2017
DOI: 10.1038/s41598-017-10167-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profile for health risk assessment: Environmental exposure to persistent organic pollutants strongly affects the human blood microRNA machinery

Abstract: Persistent organic pollutants (POPs) are synthetic chemical substances that accumulate in our environment. POPs such as polychlorinated biphenyls (PCBs), hexachlorobenzene (HCB) and dichlorodiphenyltrichloroethane (DDT) have been classified as carcinogenic to humans and animals. Due to their resistance to biodegradation humans are still exposed to these compounds worldwide. We aim to evaluate the miRNA and transcriptomic response of a human population exposed to POPs. The miRNA and transcriptomic response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Accumulating evidence has demonstrated that aberrant expression of miR-34a regulates the progression of various neoplasms (25), including glioma (26), breast cancer (27,28), cervical cancer (29), cholangiocarcinoma (30) and multiple myeloma (31). The results of the present study demonstrated that the expression level of miR-34a was reduced in RB tissues compared with that in paracarcinoma tissues (P<0.05).…”
Section: Discussionsupporting
confidence: 51%
“…Accumulating evidence has demonstrated that aberrant expression of miR-34a regulates the progression of various neoplasms (25), including glioma (26), breast cancer (27,28), cervical cancer (29), cholangiocarcinoma (30) and multiple myeloma (31). The results of the present study demonstrated that the expression level of miR-34a was reduced in RB tissues compared with that in paracarcinoma tissues (P<0.05).…”
Section: Discussionsupporting
confidence: 51%
“…Several studies have thus highlighted the impact of environmental exposure on gene expression profiles, (van Leeuwen et al, 2006) DNAmethylation patterns, (Georgiadis et al, 2016) and p53 status (Intarasunanont et al, 2012). More recently, environmental exposureinduced alterations in microRNA (miRNA) levels have been described (Krauskopf et al, 2017a). These small non-coding RNAs are involved in the posttranscriptional regulation of gene expression, and consequently are involved in virtually all cellular processes (Bartel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following the frequent inclusion of epigenetics as a parameter in environmental epidemiology studies, numerous reports have been made in recent years associating alterations in DNA methylation with various environmental factors, including biological agents, dietary habits, and air pollution (Ambatipudi et al 2016;Barouki et al 2018;de FC Lichtenfels et al 2018;Degli Esposti et al 2017;Fasanelli et al 2019;Feil and Fraga 2012;Hattori and Ushijima 2016;Herceg et al 2018;Martin and Fry 2018;Perrier et al 2019;Woo et al 2018). Similarly, many reports indicate that microRNA (miRNA) profiles are responsive to various environmental exposures, including air pollution ; Espín-Pérez et al (2018), both epidemiological studies], nanoparticles [Brzóska et al (2019), utilizing human liver cells], endocrine disruptors, such as bisphenol A (BPA) [Chou et al (2017), using human endometrial cells, and Martínez-Ibarra et al (2019), using human blood samples], and dichlorodiphenyltrichloroethane (DDT) [Krauskopf et al (2017), using human blood]. Long noncoding RNAs (lncRNAs), although still a relatively new area of research, have been reported to be associated with levels of phthalates in first trimester urine of pregnant women (LaRocca et al 2014), benzene in seven exposed individuals (Bai et al 2014b), and occupational exposure to cadmium (Zhou et al 2015) and to be responsive to developmental exposure to BPA in mice (Kumamoto and Oshio 2013) and to certain heavy metals in in vitro (Tani et al 2014;Zhou et al 2015) and in vivo experimental systems (Zhou et al 2015).…”
Section: Environmental Toxicants As Disruptors Of Epigenetic Regulationmentioning
confidence: 99%